The Fictional Guide to Impossible Truths - Guilherme Araújo Cardoso; Francisco Augusto Nogueira Lages (Principia: An International Journal of Epistemology)
In this paper, our main goal is to present a new account for contradictions and impossible truths. It is loosely based on both Austin’s account of truth and the Logic of Impossible Truths (LIT), a formal semantics designed to address incomplete, inconsistent, and non-normal sets of sentences. Our main thesis is that some truths are impossible (in the sense that they accurately classify impossible situations), but no impossibility is real, no impossible truth is about real situations. We divide the paper into four sections. In section 1, we motivate the Riddle of Impossible Truths as a general observation based on paradoxes, counterpossibles and impossible fictions. In section 2, we present our account of impossible truths, drawing on LIT and Austin’s views on truth and propositions. Section 3 is dedicated to reflecting on the artifactual nature of impossible situations. We also argue, based on Knuuttila’s ideas about models, that impossible situations serve as epistemic tools. Finally, in section 4, we conclude the paper with some thoughts on future directions for research.